Analisis gender terhadap kebiasaan makan dan faktor-faktor yang mempengaruhi perilaku positif pelajar sekolah menengah di Kota Bogor - Herien Puspitawati (Media Gizi dan Keluarga, 2008)
The purpose of this study was to examine the impacts of family socio¬economic and family relations toward adolescent's positive behaviors. The study was conducted in 2001-2003 at four technical high schools and one senior high school in Bogor City. The samples used in this study were 667 students (540 males and 127 females). The sampling method applied was simple random sampling among second graders. The study finds out that male students tended to have higher family economic pressures than female students. The proportion of female students who had vegetables intake consumption more than once a day was higher than male students; The proportion of female students who had intake consumption of protein, tea, coffee, and snacks was higher than male students; however the proportion of male students who smoke and drank alcohol was higher than female students. In general, it could be known that female students tended to have higher positive behaviors and better parenting practices by parents (warmth and support by both fathers and mothers) than male students; and there was no significant differences in parents and child relations between male and female students. Positive behaviors of students were directly affected by the higher quality of parents and child relations (for male students was affected by the quality of father-son relations, and for female students was affected by the quality of mother-doughter relations). Finally, positive behaviors of students were indirectly affected by warmth and support parenting practices done by father and mother. Then, the gender relations within family could produce the outcome of child positive behaviors. Based on these findings, it is suggested that parents (father and moyher) must optimize their functions of child socialization and parenting practices based on warmth and support toward their child so that their child's psycho-social developments could be achieved optimally